Measuring Pain for Patients Seeking Physical Therapy: Can Functional Magnetic Resonance Imaging (fMRI) Help?. Issue 1 (28th July 2016) - Elliott, James M.; Owen, Meriel; Bishop, Mark D.; Sparks, Cheryl; Tsao, Henry; Walton, David M.; Weber, Kenneth A.; Wideman, Timothy H.
Abstract: In the multidisciplinary fields of pain medicine and rehabilitation, advancing techniques such as functional magnetic resonance imaging (fMRI) are used to enhance our understanding of the pain experience. Given that such measures, in some circles, are expected to help us understand the brain in pain, future research in pain measurement is undeniably rich with possibility. However, pain remains intensely personal and represents a multifaceted experience, unique to each individual; no single measure in isolation, fMRI included, can prove or quantify its magnitude beyond the patient self-report. Physical therapists should be aware of cutting-edge advances in measuring the patient's pain experience, and they should work closely with professionals in other disciplines (eg, magnetic resonance physicists, biomedical engineers, radiologists, psychologists) to guide the exploration and development of multimodal pain measurement and management on a patient-by-patient basis. The primary purpose of this perspective article is to provide a brief overview of fMRI and inform physical therapist clinicians of the pros and cons when utilized as a measure of the patient's perception of pain. A secondary purpose is to describe current known factors that influence the quality of fMRI data and its analyses, as well as the potential for future clinical applications relevant to physical therapist practice. Lastly, the interested reader is introduced and referred to existing guidelines and recommendations for reporting fMRI research.